Circulation and fjord-shelf exchange during the ice-covered period in Young Sound-Tyrolerfjord, Northeast Greenland (74°N). (15th July 2017) - Boone, W.; Rysgaard, S.; Kirillov, S.; Dmitrenko, I.; Bendtsen, J.; Mortensen, J.; Meire, L.; Petrusevich, V.; Barber, D.G.
Abstract: Fjords around Greenland connect the Greenland Ice Sheet to the ocean and their hydrography and circulation are determined by the interplay between atmospheric forcing, runoff, topography, fjord-shelf exchange, tides, waves, and seasonal growth and melt of sea ice. Limited knowledge exists on circulation in high-Arctic fjords, particularly those not impacted by tidewater glaciers, and especially during winter, when they are covered with sea-ice and freshwater input is low. Here, we present and analyze seasonal observations of circulation, hydrography and cross-sill exchange of the Young Sound-Tyrolerfjord system (74°N) in Northeast Greenland. Distinct seasonal circulation phases are identified and related to polynya activity, meltwater and inflow of coastal water masses. Renewal of basin water in the fjord is a relatively slow process that modifies the fjord water masses on a seasonal timescale. By the end of winter, there is two-layer circulation, with outflow in the upper 45 m and inflow extending down to approximately 150 m. Tidal analysis showed that tidal currents above the sill were almost barotropic and dominated by the M2 tidal constituent (0.26 m s −1 ), and that residual currents (∼0.02 m s −1 ) were relatively small during the ice-covered period. Tidal pumping, a tidally driven fjord-shelf exchange mechanism, drives a salt flux that is estimated to range between 145 kg s −1 and 603 kg s −1 . Extrapolation of these values over the ice-covered period indicates that tidal pumping is likely a major source of dense water and driver of fjord circulation during the ice-covered period. Highlights: Seasonal observations from ice tethered moorings in an ice-covered fjord in Northeast Greenland. Circulation and tidal exchange of salt across a shallow outer sill. Renewal of water masses in the fjord on a seasonal timescale.